Information communication technology (ICT), smart urbanization, and environmental quality: Evidence from a panel of developing and developed economies - Chatti, Walid; Majeed, Muhammad Tariq (Journal of cleaner production, 2022)
Urbanization is a fundamental driver of sustained economic growth, but uncontrolled urbanization without appropriate information and communication technology (ICT) and transport networks leads to undesirable effects, such as pollution, accidents, and congestion. This study extends the environmental literature by investigating whether ICT helps to improve environmental protection when adopted in urban areas, using a panel dataset comprising 60 developing and 34 developed countries between 1998 and 2016. Empirically, we employ the 2-step system Generalized Method of Moments (GMM) strategy including two empirical specifications: with and without control variables. The estimates show that (1) ICT adoption within urban areas can improve environmental quality for developing and developed countries. For instance, a 10% rise in the interaction between ICTs and urbanization can reduce pollution between 1% and 6.5% for developed countries. (2) The variables urbanization and ICTs negatively affect environmental protection. (3) Telephone use within urban areas is more efficient in reducing environmental damages compared to mobile phones and internet technologies. (4) The positive effect of the interaction between ICTs and urbanization is very weak for developing economies. A 10% rise in the association between urbanization and ICTs can reduce pollution by between 0.1% and 1%. Public policies should concentrate on the adoption of ICT inside urban areas to ensure environmental protection. The integration of the smart cities approach can help in reducing urban pollution. [Display omitted] •The role of ICT adoption in urban areas is explored using a panel data of world economies.•Urbanization negatively affects environmental protection.•ICT adoption within urban areas can improve environmental quality.•Telephone use within urban areas is more efficient in reducing environmental damages.•The environment improving effect of ICT is very weak for developing economies.